Implementation of a Smoking Cessation Program to Improve Knowledge, Attitudes, and Behavior Among Gresik Students - Rofi'ah, Eviyana; Budiono, Irwan; Rahayu, RR. Sri Ratna; Sofyan, Afriyadi (Public Health Perspective Journal, 2025)
Tobacco use among adolescents remains a serious public health concern, especially in developing countries like Indonesia. This study aims to evaluate the impact of a school-based smoking cessation program on students' knowledge, attitudes, and smoking behavior in Gresik. A quasi-experimental design with pre-test and post test was applied to 142 high school students, divided into experimental and control groups. The intervention included educational sessions, discussions, and practical tools for quitting smoking. Data were analyzed using the Wilcoxon test, revealing significant improvements across all measured variables: knowledge (p = 0.000), attitudes (p = 0.000), and smoking behavior (p = 0.000). The findings demonstrate the program’s effectiveness in increasing awareness about the dangers of smoking, promoting negative attitudes toward smoking, and reducing cigarette consumption among participants. These results indicate the potential of school-based interventions to produce meaningful behavioral change in adolescents. The study contributes to public health knowledge by highlighting the importance of targeted, structured programs in reducing smoking prevalence among youth and suggests the need for broader implementation and long-term follow-up strategies to maintain positive outcomes.